2003
DOI: 10.1080/0954012031000105478
|View full text |Cite
|
Sign up to set email alerts
|

With health comes work? People living with HIV/AIDS consider returning to work

Abstract: Many people living with HIV/AIDS (PHAs) ham experienced significant improvements in their health over the last few years, to the point that many are considering returning to work. The objectives of this study were to develop a model of return to work which could apply to chronic illnesses with a fluctuating or uncertain course. Issues related to health, work and return to work were explored using in-depth interviews with 20 PHAs in Toronto, Canada, who had been on long-term disability for at least five years. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 9 publications
3
41
0
Order By: Relevance
“…First, HIV infection may constitute a barrier to access (or return) to work for those unemployed: studies have reported that although large proportions of unemployed HIV-infected persons have contemplated work re-entry as efficient treatments have emerged, few have actually done so [28,[34][35][36][37]. Moreover, HIV disease may constitute a cause of employment loss.…”
Section: Discussionmentioning
confidence: 99%
“…First, HIV infection may constitute a barrier to access (or return) to work for those unemployed: studies have reported that although large proportions of unemployed HIV-infected persons have contemplated work re-entry as efficient treatments have emerged, few have actually done so [28,[34][35][36][37]. Moreover, HIV disease may constitute a cause of employment loss.…”
Section: Discussionmentioning
confidence: 99%
“…[17] There are only a handful of HIVspecific employment programs in North America concentrated in large urban centres, and much work is required to address inconsistent benefit and income support structures that influence the employment options of many PHAs. [1] The most recent literature reviews and syntheses conducted by and Werth (2008) identified very few articles related to the needs and barriers influencing return to work for PHAs and the vocational services designed to address them. [3,26] Thus, very little research evidence exists to inform social policy and effective community programming that could support the employment-related needs of PHAs.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Recent studies suggest that approximately half (42%-62%) of PHAs in industrialized countries are unemployed. [4][5][6][7][8] While the links between health and labour force participation are complex, it is clear that labour force participation is an important intermediate social driver and determinant of health.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In certain jurisdictions, returning to work may lead to the termination of long-term disability benefits, a drawback that is compounded by PWHIV's inability to regain these benefits in the event that their health begins to deteriorate. Preoccupation with this potential loss of financial security can lead to increased stress and worry, to the point of debilitating PWHIV in their vocational decision-making (Brooks et al, 2004;Ferrier & Lavis, 2003). Brooks et al (2004) concluded that, of a sample of 536 unemployed PWHIV, 73% of those contemplating a return to work ranked the fear of losing their disability income as the most significant barrier to the resumption of professional activities.…”
Section: The Vocational Task In the Context Of Adaptation To Hiv/aidsmentioning
confidence: 99%